GNSS User Technology Report 2020 - Marco Lisi (mediaGEO soc. coop., 2021)
The article introduces and summarizes the GNSS User Technology Report - 3rd Edition, recently issued by the European GNSS Agency (GSA). The report is a true mine of information about the Global Navigation Satellite Systems presently operational, their major services and applications, and the state-of-the-art of the user receivers.